The Influence of Work Supervision, Leadership Style, Motivation nd Organizational Culture n Employee Achievement at School - Rizkawati, Nidya; Rachmawati, Eny (International Journal on Advanced Science, Education, and Religion, 2024)
The purpose of this study was to determine the factors that influence employee performance at the Permata Mojokerto Integrated Islamic School, which include work supervision factors, leadership style, work motivation and organizational culture. This research method is a method with a quantitative approach involving 33 employees at the Permata Mojokerto Integrated Islamic School using saturated sampling techniques or censuses. Data collection was carried out using questionnaire distribution. The data obtained were analyzed using a statistical formula, namely by using multiple regression analysis whose processing was carried out with the SPSS 25 program. Based on the test results with the SPSS 25 program, the multiple linear regression equation is known as follows: Y = - 1.342 + 0.591X1 + 0.334X2 + 0.843X3 + 0.727X4. The work supervision variable has a significant effect on employee work performance at Permata Mojokerto Integrated Islamic School. The leadership style variable has a significant effect on employee work performance at Permata Mojokerto Integrated Islamic School. The work motivation variable has a significant effect on employee work performance at Permata Mojokerto Integrated Islamic School. The organizational culture variable has a significant effect on employee work performance at Permata Mojokerto Integrated Islamic School. The work supervision, leadership style, work motivation and organizational culture variables simultaneously affect employee work performance at Permata Mojokerto Integrated Islamic School, with a significant value of 0.000 which is smaller than 0.05. Keywords: Work Supervision, Leadership Style, Work Motivation, Culture Organization and Work Performance of Officers